Сompatibility of Systemic Drugs and Local Antihypertensive Therapy in Patients with Primary Open-Angle Glaucoma (Analytical Review) - V. P. Erichev; A. S. Makarova (Oftalʹmologiâ, 2019)
The review presents data of the most common comorbid diseases in patients with primary open-angle glaucoma, the features of local and general influence of antiglaucoma drugs, as well as information about the possible drug interactions of local antihypertensive and systemic medicines. Local antihypertensive drugs are often embedded in the daily patients regimen of systemic drugs use. Up to80 % of the active substances in ophthalmic drugs are absorbed systemically, while not subject to the primary stages of metabolism. Anti-glaucoma drugs can cause serious side effects: symptomatic bradycardia, various conduction disturbances in the heart muscle, orthostatic hypotension, syncope, dyspeptic symptoms, exacerbation of chronic diseases of the liver and kidneys, etc. In clinical studies, it was shown that the level of timolol in blood plasma correlates with the development of side effects from the cardiovascular system. In everyday ophthalmic practice, β-blockers are considered as drugs with a minimal number of adverse events, they are the most widely used in hypotensive glaucoma therapy. But another thing is also known: receptors for β-adrenergic blockers are present in almost all organs and tissues of the body. This circumstance determines the frequency, prevalence and nature of adverse events associated with β-blockers intake. with simultaneous systemic and topical application of β-blockers, mutual enhancement of effects is possible (additional IOP decrease and enhancement of β-adrenergic blocking effect on the cardiovascular system). If β₁-, β₂-adrenergic blockers and adrenergic psychotropic drugs should be used together with caution: the latter affect peripheral innervation, the α-adrenoblocking effect is most pronounced, resulting in a decrease in the strength of heart contractions, a drop in blood pressure until orthostatic hypotension develops. All mentioned above must be considered for choosing and prescribing antiglaucoma drugs. It increases compliance, patient’s quality of life and allows to stabilize the glaucomatous process.